How does stellate ganglion block alleviate immunologically-linked disorders?. (November 2020) - Lipov, Eugene; Gluncic, Vicko; Lukić, Ivan K.; Candido, Kenneth
Abstract: Background: The stellate ganglion is an autonomic nervous ganglion, formed by the fusion of the inferior cervical sympathetic ganglion and the first thoracic sympathetic ganglion, which is present in about 80% of people. It is anterior to the neck of the first rib and contains neurons that supply sympathetic innervation to the head and neck. Injection of local anesthetics near the stellate ganglion (stellate ganglion block; SGB) has been used for multiple clinical indications including sympathetic-mediated pain and vascular insufficiency syndromes of the upper extremity. In addition, reports on SGB having significant impact on conditions linked to immune dysfunction have been published for a century, but the mechanisms of SGB action have been poorly understood. Hypothesis: SGB hinders the sympathetic innervation of the immune organs, thus modulating the immune system activity and leading to the alleviation of the disease. Evidence: All primary (thymus and bone marrow) and secondary immune organs (spleen, lymph nodes, mucosa-associated lymphoid tissue) receive a substantial sympathetic innervation, with norepinephrine (NE), as the main neurotransmitter. Complementarily, T and B lymphocytes express β2-adrenergic receptors, while innate immune cells express both α- and β-adrenergic receptors. The consequences of adrenergic receptor signaling can be summarized as immuno-modulatory. Activation of adrenergic receptors leads to decreased levels of pro-inflammatory cytokines (e.g. IL-1β, IL-6, TNF-α) and increased levels of anti-inflammatory cytokines, like IL-10 or TGF-β. Cellular changes include increase in the number of regulatory T cells and shift of the Th1/Th2 balance towards the Th2 response. Since the changes in immune response are global, the explanation has to include generalization of the SGB effect. A likely explanation includes centripetal neuronal pathways between the stellate ganglion and deep brain regions such as insula, amygdala, and hippocampus. Those, in turn, have reciprocal innervation with locus ceruleus, a brain-stem structure involved in the control of the autonomous nervous system. Conclusion: Various pathologic conditions have been shown to be SGB responsive, where the symptoms have been reduced or eliminated. Many of those clinical improvements have been mirrored by measurable immunologic changes. A plausible explanation, consistent with the evidence available so far, is that SGB exerts its effects by regulating the immune system, through a central, reflex-like pathway. Our hypothesis provides a theoretical framework for understanding the effects of SGB and could, thus lead to wider usage of the technique in immune-linked disorders such as ulcerative colitis.